2022
DOI: 10.5713/ab.21.0327
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating productive performance, meat quality and oxidation products of Italian White breed rabbits under free-range and cage rearing system

Abstract: Title of the manuscript: Evaluating productive performance, meat quality and oxidation products of Italian White breed rabbits under free-range and cage rearing system ABSTRACT Objective: Free-range systems have been increasingly available to the consumer due to increased demand for more sustainable meat-products. In the current study, it was explored the effect of free-range (FR) and cage system (CS) on growth performance, meat quality and oxidation products in Italian White breed rabbits during the growing-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The level of protein carbonyls of broiler meat fed DOP indicated optimal oxidative reactions. Moreover, protein oxidation seems to be influenced by the level of lipid oxidation in meat ( Tufarelli et al, 2022 ). The levels of thiobarbituric acid-reactive substances observed in the present study were correlated with carbonyl proteins levels.…”
Section: Resultsmentioning
confidence: 99%
“…The level of protein carbonyls of broiler meat fed DOP indicated optimal oxidative reactions. Moreover, protein oxidation seems to be influenced by the level of lipid oxidation in meat ( Tufarelli et al, 2022 ). The levels of thiobarbituric acid-reactive substances observed in the present study were correlated with carbonyl proteins levels.…”
Section: Resultsmentioning
confidence: 99%
“…Although this is a preliminary study that only analyses different rearing systems based on assessing welfare through ABMs (cortisol and IL-6), it offers plenty of food for thought. Indeed, as illustrated by other authors [54][55][56], the effects on rabbit growth performance, as well as on carcass and meat quality [56][57][58], showed that animals housed in cages had: (i) a higher percentage of fat deposits, (ii) better production than rabbits raised in large pens, and (iii) a higher weight at slaughter [59].…”
Section: Discussionmentioning
confidence: 79%
“…In addition, rabbit meat is more prone to lipid oxidation than other meats, and it can easily permit the growth of pathogenic and spoilage microorganisms [ 42 , 44 ]. Tufarelli et al [ 11 ] found that muscles from FR rabbits showed an improvement in the oxidative stability in respect to the group reared in conventional cage. In particular, the meat from FR rabbits had a lower thiobarbituric acid-reactive substances level compared to CS rabbits, suggesting that the housing system may fortify the meat oxidative stability.…”
Section: Discussionmentioning
confidence: 99%
“…The research was conducted in an experimental rabbitry located in the province of Bari, Apulia region (Italy). Forty male Italian White ( Bianca Italiana ) breed rabbits, obtained from the Central Breeding Farm of the Italian Rabbit Breeders Association (ANCI-AIA, Volturara Appula, Foggia, Italy) and aged 35 days (body weight 1,045±10.1 g, mean± standard error of the mean), were randomly assigned to two groups of 20 animals according to the rearing system: FR and CS as in our previous study [ 11 ]. Briefly, within each group, rabbits were divided into five replicates having four rabbits/replicate, for a total of 20 rabbits per group.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation